1998
DOI: 10.1074/jbc.273.19.11758
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evidence That Small Proline-rich Proteins and Trichohyalin Function in Epithelia by Modulation of the Biomechanical Properties of Their Cornified Cell Envelopes

Abstract: The cornified cell envelope (CE) is a specialized structure involved in barrier function in stratified squamous epithelia, and is assembled by transglutaminase crosslinking of several proteins. Murine forestomach epithelium undergoes particularly rigorous mechanical trauma, and these CEs contain the highest known content of small proline-rich proteins (SPRs). Sequencing analyses of these CEs revealed that SPRs function as cross-bridgers by joining other proteins by use of multiple adjacent glutamines and lysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
130
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 53 publications
4
130
0
1
Order By: Relevance
“…The various members of the SPR classes display wide variations of expression in different epithelia. For example, SPR1a (cornifin α) and certain SPR2 proteins are expressed in dry epithelia such as the epidermis; distinctly different members of the SPR2 class are expressed in internal epithelia; and SPR3 is abundantly expressed in mucosal epithelia exposed to mechanical stress, such as the esophagus and rodent forestomach, while it is absent in the epidermis (Fujimoto et al, 1993;Hohl et al, 1995;Steinert et al, 1998b;Song et al, 1999). However, most members are induced in response to UV damage and phorbol esters (Kartasova and van de Putte, 1988;Kartasova et al, 1988b;Gibbs et al, 1990) or malignancy (Yaar et al, 1995).…”
Section: Structural Protein Components Of Cesmentioning
confidence: 99%
See 1 more Smart Citation
“…The various members of the SPR classes display wide variations of expression in different epithelia. For example, SPR1a (cornifin α) and certain SPR2 proteins are expressed in dry epithelia such as the epidermis; distinctly different members of the SPR2 class are expressed in internal epithelia; and SPR3 is abundantly expressed in mucosal epithelia exposed to mechanical stress, such as the esophagus and rodent forestomach, while it is absent in the epidermis (Fujimoto et al, 1993;Hohl et al, 1995;Steinert et al, 1998b;Song et al, 1999). However, most members are induced in response to UV damage and phorbol esters (Kartasova and van de Putte, 1988;Kartasova et al, 1988b;Gibbs et al, 1990) or malignancy (Yaar et al, 1995).…”
Section: Structural Protein Components Of Cesmentioning
confidence: 99%
“…All SPRs are built from a variable number of eight (in SPR1 and SPR3) or nine (in SPR2) amino acid residue proline-rich repeats. The number of repeats ranges from three in human SPR2 to 23 in human SPR3, so that the mass of SPRs varies between 6 kDa to 25 kDa (Fujimoto et al, 1993;Gibbs et al, 1993;Austin et al, 1996;Kartasova et al, 1996;Steinert et al, 1998b;Song et al, 1999). The repeats are flanked by short glutamine-, lysine-and proline-rich amino and carboxy terminal domains showing distant homology to the head and tail regions in involucrin and loricrin (Gibbs et al, 1993).…”
Section: Structural Protein Components Of Cesmentioning
confidence: 99%
“…21 Furthermore, we have found a correlation between the amount of SPR proteins used in CEs and the presumed physical requirements for mechanical strength and toughness of the epithelium. 10 From this, we have concluded that the SPRs serve as biomechanical modifiers of the physical properties of the CE structures in order to fulfill the particular requirements of different epithelia to withstand physical trauma. 10 Recent biochemical experiments have shown that for the SPR1 16 and SPR2 17 proteins, each TGase enzyme preferentially cross-links certain glutamine and lysine residues with high specificity, from which we could conclude that multiple enzymes are required to cross-link them in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…10 From this, we have concluded that the SPRs serve as biomechanical modifiers of the physical properties of the CE structures in order to fulfill the particular requirements of different epithelia to withstand physical trauma. 10 Recent biochemical experiments have shown that for the SPR1 16 and SPR2 17 proteins, each TGase enzyme preferentially cross-links certain glutamine and lysine residues with high specificity, from which we could conclude that multiple enzymes are required to cross-link them in vivo. Moreover, in the case of SPR1 proteins, the data imply an obligatory temporal order to this process: first cross-linking by the cytosolic TGase 3 into short oligomers, which in turn are later cross-linked by the membrane-associated TGase 1 enzyme into large polymers onto the CE barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Human LOR is an insoluble protein initially expressed in the granular layer of the epidermis during cornification, and comprises 80% of the total protein mass of the cornified envelope (CE) [7,[13][14][15][16]. Additionally, LOR functions as a main reinforcement protein for the CE and is deposited onto a scaffold of IVL and other calcium-binding proteins [17].…”
Section: Introductionmentioning
confidence: 99%